GaSbBi Metal Semiconductor Metal Detectors for Mid-Infrared Sensing - Cao, Zhongming; Hulme, Sorcha; Veal, Tim D.; Ashwin, Mark J.; Sandall, Ian (Frontiers in Electronic Materials, 2022)
The viability of incorporating Bismuth and Nitrogen into GaSb layers to realise photodetectors operating in the mid infrared has been investigated. The effects of Bi and N on the cutoff wavelength of GaSb based metal semiconductor metal photodetectors has been evaluated. The spectral responsivity measurements indicate a clear wavelength extension, with only a relatively modest reduction in the external quantum efficiency. Comparisons of the spectral response characteristics indicate that Bi incorporation reduces the carrier extraction and the impact of this on future device design is considered.